Hubungan Motivasi Ibu, Kualitas Layanan KB Dan Peran Bidan Terhadap Perilaku Penggunaan Metode Kontrasepsi Jangka Panjang (MKJP) Di Puskesmas Lenteng Agung Jakarta Selatan : The Relationship between Maternal Motivation, Quality of Family Planning Services and the Role of Midwives on the Behavior of Using Long Term Contraceptive Methods (MKJP) at the Lenteng Agung Community Health Center, South Jakarta - Bere Mau, Viktoria Angelina (Indonesian Scholar Journal of Nursing and Midwifery Science (ISJNMS), 2024)
Introduction: Long Term Contraceptive Devices (MKJP) are contraceptive devices used to delay, space out pregnancies, and stop fertility that are used for a long period of time including IUD (Intra Uterine Device), Implant (KB implant), and Kontap (steady contraception). In socializing the contraceptives that will be used by family planning acceptors, the effectiveness of counseling by health workers, especially midwives, is greatly determined. The family planning program not only aims to control the rate of growth, but also to meet the public's demand for quality family planning and reproductive health (KR) services, reducing maternal mortality (AKI) and infant mortality (IMR) as well as overcoming reproductive health problems to form a family small quality. The aim of this research is to determine the relationship between maternal motivation, quality of family planning services and the role of midwives on the behavior of using long-term contraceptive methods (MKJP) at the Lenteng Agung Community Health Center, South Jakarta.  Methods: This type of research is analytical descriptive research using quantitative methods with a cross sectional approach. The population in this study was all 117 family planning acceptors who came to the Lenteng Agung Health Center, South Jakarta. The sampling technique in this research is random sampling. So, the sample in this study was 35 respondents. The instrument in this research is to use a questionnaire. Data analysis in this study used the chi-square test. Results: The results show that of the 35 respondents' behavior in selecting Long-Term Contraceptive Methods (MKJP) most of them behaved fairly 15 people (42,9%). The results of the mother's motivation obtained a p-value = 0,016; the quality of family planning services obtained a p-value = 0,006; the role of the midwife obtained a p-value = 0,000. Discussion: There is a relationship between maternal motivation and behavior in selecting Long Term Contraceptive Methods (MKJP) at the Lenteng Agung Jakarta Health Center. There is a relationship between the quality of family planning services and the behavior of selecting Long Term Contraceptive Methods (MKJP) at the Lenteng Agung Community Health Center. There is a relationship between the role of midwives and the behavior of selecting Long Term Contraceptive Methods (MKJP) at the Health Center in Lenteng Agung, Jakarta.